Usability-Based User-Centered Design of Android Applications - Kar, Swagatika (International Journal of Scientific Research and Management (IJSRM), 2016)
Usability is a quality attribute which makes the user interfaces easier to use. Now-a-days the use of mobile devices in increasingrapidly, which are mostly used by common people. So these mobile devices and their applications must have good usability features toachieve wide acceptance by the users. MobileHCI community has proposed various recommendations for these usability features to beincluded at the time of development to improve the usability. But there is a significant gap lying between the mobileHCI community andapplication development teams since many years. Many attempts have been made to bridge this gap. Our proposed work provide guidelinesto the development teams of Android applications for including various usability features into their applications.